Evaluation Of User Experience And Recommendation Of Improvements To The Jember DISPENDUKCAPIL Service Information System With UEQ Method - Selly Mandalica Gucci; Fahrobby adnan (Faculty of Computer Science, University of Jember, 2022)
SIP Dispendukcapil Jember is a mobile application released in 2019 by the Jember Regency Government to make it easier for the public to manage and register civil. This study uses the UEQ method which has 6 parameters with 26 items, the UEQ parameters include Attractive, Perspicuity, Efficiency, Dependability, Stimulation, and Noveltyn with the result being a recommendation for feature improvements to be improved again. This research started from data collection, literature study, respondent determination, instrument preparation, data collection strategy development, UEQ questionnaire distribution, evaluation data analysis using the UEQ method, compiling recommendations for improvement and the result is an Attractive value of 1.26 which is above the average criteria, Perspicuity 1.35 above the average criteria, Efficiency 0.97 below the average criteria, Dependability 0.89 included in the criteria. below the average criteria, 1.11 Stimulation is included in the below average criteria. the above average criteria, Novelty 1.19 is a good criterion.